Establishment and maturation of gut microbiota in White King pigeon squabs: role of pigeon milk - Xu, Xiaoqin; Wang, Zihan; Jian, Yi; Zhang, Long; Zhou, Caiquan; Liu, Li; Liu, Hui (Frontiers in Microbiology, 2025)
BackgroundPigeons are significant economic animals in China; however, research regarding the establishment and influencing factors of gut microbiota in squabs remains limited. Understanding how the gut microbiota develops in pigeons, particularly in relation to pigeon milk, is importance in pigeon production. This study aims to elucidate the establishment characteristics of the gut microbiota in White King pigeon squabs and explore the role of pigeon milk in this process.MethodsThis study employed 16S rRNA sequencing technology to investigate the dynamics of microbial composition in feces and pigeon milk at various growth stages of White King pigeon. Functional prediction analysis was performed to assess the metabolic pathways involved, and correlation analysis was used to explore the relationships between microbial communities in different sample types.ResultsThe findings revealed a diverse microbiome present in the meconium of newborn pigeons, with a microbial composition that significantly differed from that of other feces groups. In contrast, the microbial composition of feces (FN) from pigeons aged 7 to 21 days exhibited less variability. At the phylum level, the predominant microbial taxa identified in the feces of FN were Firmicutes, Actinobacteriota, and Proteobacteria. At the genus level, the main dominant bacterial groups included Lactobacillus, Limosilactobacillus, and Turicibacter. Functional prediction analysis indicated that the gut microbiota of pigeons primarily participate in metabolic pathways related to carbohydrates, amino acids, lipids, cofactors, and vitamins. Furthermore, the dominant bacteria found in pigeon milk (MN) were identified as probiotics, including Limosilactobacillus, Ligilactobacillus, Lactobacillus, Bifidobacterium, and Aeriscardovia, which collectively accounted for over 90% of the total abundance. Correlation analysis of the abundance of shared microbes revealed that the association between meconium and feces at the other stages was extremely low. In contrast, the correlation between colostrum and feces at the post-feeding stage were found to be the highest.ConclusionThis study indicates that prenatal colonization occurs in White King pigeons. Notably, within the first week after birth, the gut microbial composition of young pigeons becomes stable. Furthermore, the colostrum serves as the most significant driver for the establishment of intestinal microbiota in squab post-birth. The findings of this study suggest that microorganisms can be added to artificial pigeon milk based on the predominant microbial composition of colostrum. This approach could facilitate the establishment of gut microbiota in young pigeons, thereby promoting their growth and development and providing production benefits.